Lecturer Performance Measurement Based on Organizational Culture and Leadership Behavior Analysis Using Pearson Correlation - Ni Luh Putri Srinadi; Luh Putu Wiwien Widhyastuti; Dandy Pramana Hostiadi; Candra Ahmadi (Journal of Innovation in Educational and Cultural Research, 2024)
The academic institution generally has management quality to measure lecturer performance. It can be estimated from two variables: leadership behavior and organizational culture. This variable needs to be analyzed to determine the relationship between its parameters and forms as correlations strength for identifying the lecturer's performance. This paper proposed a new approach to measure a correlation with two variables, namely the leadership variable and the organizational culture variable. Correlation measurement adopts the Pearson Correlation. It aims to define the correlation strength. Thus, it can show the quality of lecturer performance in an academic institution. Correlation measurement uses seven parameters on leadership variables and seven measurement parameters from organizational culture variables. The experiment shows that five parameter pairs in the two variables have a strong correlation. The highest positive correlation strength is obtained at 0.321 in routine evaluation with behavior parameters. The approaches can be used to determine the lecturer's reward.